Spatial–temporal evolution and driving mechanism in soybean production patterns: a case study of Inner Mongolia, China - Hu, Juanjuan; Zhang, Jianjun (Frontiers in Sustainable Food Systems, 2025)
IntroductionAnalyzing the spatial–temporal evolution law and driving mechanism of soybean production patterns in Inner Mongolia provides a decision-making basis for optimizing agricultural structures and ensuring regional food security in arid and semi-arid regions.MethodsThe study comprehensively utilized the logarithmic mean divisia index, spatial Gini coefficient, industrial concentration rate, and gravity center migration model to reveal the spatial–temporal evolution characteristics of county-level soybean production patterns across Inner Mongolia from 2002 to 2022, and established a spatial Durbin model to explore the multi-dimensional driving mechanism underlying the spatial–temporal pattern evolution of soybean production.ResultsThe findings illustrated: (1) Temporally, soybean production capacity in Inner Mongolia has generally shown an upward trend, progressing through four distinct stages—fluctuating adjustment, yield breakthrough, scale expansion, and transformation-optimization. (2) Spatially, soybean production exhibits an overall distribution pattern of “eastern concentration and central-western diffusion,” with persistently high spatial agglomeration and a shifting gravity center within the agricultural belt along the eastern foothills of the Greater Khingan Mountains. (3) Regarding driving factors, the expansion of the sown area served as the primary internal driver of production growth. Meanwhile, external factors—including precipitation, cultivated land resources, regional economic development, comparative benefits of agriculture and soybeans, labor scale, mechanization level, fertilizer input, and fiscal expenditure—significantly influenced the production landscape.ConclusionPolicy recommendations for optimizing the soybean production layouts in Inner Mongolia were proposed from the dimensions of consolidating the advantages of production areas, reinforcing technological innovation, deepening regional collaboration and optimizing fiscal mechanisms.